The association between prenatal per-and polyfluoroalkyl substance levels and Kawasaki disease among children of up to 4 years of age: A prospective birth cohort of the Japan Environment and Children’s study - Hiroyoshi Iwata; Sumitaka Kobayashi; Mariko Itoh; Sachiko Itoh; Rahel Mesfin Ketema; Naomi Tamura; Chihiro Miyashita; Takeshi Yamaguchi; Keiko Yamazaki; Hideyuki Masuda; Yu Ait Bamai; Yasuaki Saijo; et al. (Environment International, 2024)
Kawasaki disease (KD) is common among pediatric patients and is associated with an increased risk of later cardiovascular complications, though the precise pathophysiology of KD remains unknown. Per- and polyfluoroalkyl substances (PFAS) have gathered notoriety as the causal pathogens of numerous diseases as well as for their immunosuppressive effects. The present epidemiological study aims to assess whether PFAS may affect KD risk. We evaluated research participants included in the ongoing prospective nationwide birth cohort of the Japan Environment and Children’s Study (JECS). Among the over 100,000 pregnant women enrolled in the JECS study, 28 types of PFAS were measured in pregnancy in a subset of participants (N = 25,040). The JECS followed their children born between 2011 and 2014 (n total infants = 25,256; n Kawasaki disease infants = 271), up to age four. Among the 28 types of PFAS, those which were detected in >60 % of participants at levels above the method reporting limit (MRL) were eligible for analyses. Multivariable logistic regressions were implemented on the seven eligible PFAS, adjusting for multiple comparison effects. Finally, we conducted Weighted Quantile Sum (WQS) and Bayesian kernel machine regression (BKMR) to assess the effects of the PFAS mixture on KD. Therefore, we ran the BKMR model using kernel mechanical regression equations to examine PFAS exposure and the outcomes of KD. Upon analysis, the adjusted multivariable regression results did not reach statistical significance for the seven eligible substances on KD, while odds ratios were all under 1.0. WQS regression was used to estimate the mixture effect of the seven eligible PFAS, revealing a negative correlation with KD incidence; similarly, BKMR implied an inverse association between the PFAS mixture effect and KD incidence. In conclusion, PFAS exposure was not associated with increased KD incidence.